PENERAPAN MODEL PEMBELAJARAN GUIDED INQUIRY UNTUK MENINGKATKAN KETERAMPILAN PROSSES SAINS SISWA KELAS VIII SMPN 1 PEKANBARU PADA MATERI TEKANAN ZAT - Putri, Bella; Syahril, Syahril; Irianti, Mitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrak: Abstract: This study aims to determine students' science process skills by applying the guided inquiry learning model to the substance pressure material. The research method used is a quasy experiment with a Posttest Only Control Design design. The population of this research was all students of class VIII SMPN 1 Pekanbaru. The sample was selected two classes randomly from a homogeneous population of 33 students as the experimental class and 32 students the control class. The research instrument was a test of science process skills. The data were collected through giving process skills tests to the research sample after the learning process was carried out. Data were analyzed descriptively to see the average absorption capacity of students' science process skills and inferential by using the T-test. The results showed that there was a significant difference between the science process skills of students in the class that applied the guided inquiry learning model and the class that applied the conventional one. The average score of students' science process skills in the experimental class was higher than the control class. Based on the results of this study, it can be concluded that the guided inquiry learning model can improve the science process skills of class VIII students of SMPN 1 Pekanbaru on Substance Pressure material.Key Words: Guided inquiry, Science Process skills , Tekanan Zat